2021
DOI: 10.34133/2021/2173642
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Plant-Based Ionizers in Removing Aerosol for COVID-19 Mitigation

Abstract: Small-sized droplets/aerosol transmission is one of the factors responsible for the spread of COVID-19, in addition to large droplets and surface contamination (fomites). While large droplets and surface contamination can be relatively easier to deal with (i.e., using mask and proper hygiene measures), aerosol presents a different challenge due to their ability to remain airborne for a long time. This calls for mitigation solutions that can rapidly eliminate the airborne aerosol. Pre-COVID-19, air ionizers hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“… Air Ionization ( What is a MERV rating? 2021 ; Nembhard et al, 2020 ; Uk Lee et al, 2004 ; Hyun et al, 2017 ; Sawant et al, 2012 ; Pekárek, 2003 ; Yehia et al, 2000 ; Sung et al, 2019 ; Suwardi et al, 2021 ; Agranovski et al, 2006 ) Causes a significant increase in airborne particle deposition rates. Commercially available technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Air Ionization ( What is a MERV rating? 2021 ; Nembhard et al, 2020 ; Uk Lee et al, 2004 ; Hyun et al, 2017 ; Sawant et al, 2012 ; Pekárek, 2003 ; Yehia et al, 2000 ; Sung et al, 2019 ; Suwardi et al, 2021 ; Agranovski et al, 2006 ) Causes a significant increase in airborne particle deposition rates. Commercially available technology.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is worth noting that electrostatic precipitators induce a local deposition of particles onto the collection plate, whereas a simple air ion emitter will likely cause an increased particle deposition to all surfaces within an enclosed space. Plant-based ionizers also exist and are commercially available ( Suwardi et al, 2021 ), and offer another seemingly viable and effective alternative to generate air ions without also generating ozone. The cited study reported a CADR equal to approximately 4 m 3 /min.…”
Section: Introductionmentioning
confidence: 99%
“…There results showed that the ionizer device prevented the infection spread with high efficacy in pigs ( Hagbom et al, 2015 ). Also, Suwardi and colleges demonstrated that plant-based ionizers can aid in reduction of erosol-containing virions indoors ( Suwardi et al, 2021 ). However, the wide use and potency of these air ionizing techniques are still not fully investigated.…”
Section: The Role Of Air Purification In Fighting the Covid-19 Spreadmentioning
confidence: 99%
“…More details on the experimental setup can be found in our earlier work along with a more comprehensive review by Su et al on various technologies for studying air quality. 58,59 To quantify the cumulative concentration of aerosol emitted from the fog generator, a reference sensor is always placed right in front of the opening of the fog generator. The remaining sensors are placed at various distances and directions, depending on the test scenario of interest.…”
Section: Methodsmentioning
confidence: 99%